Developing a Performance-Based Budgeting Model to Strengthen Governance in Islamic Boarding Schools - Ramdhansyah Ramdhansyah; Rosmala Dewi; Yuniarto Mudjisusatyo (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2024)
This study aims to develop a comprehensive and context-sensitive budgeting model for Islamic boarding schools, which are characterized by complex educational, religious, and socio-cultural activities extending beyond formal classroom instruction. Recognizing the limitations of conventional budgeting approaches, this research adopts a qualitative methodology using a multiple-case study design. Data were collected through in-depth interviews with leaders and managerial staff of selected Islamic boarding schools in Indonesia to explore budgeting practices, decision-making processes, and stakeholder involvement. The findings reveal that effective budgeting in Islamic boarding schools requires the integration of performance-based budgeting principles, transparency, and active participation of key stakeholders. Performance indicators aligned with institutional goals were found to enhance accountability and managerial effectiveness, while stakeholder engagement strengthened governance structures and institutional commitment. This study concludes that an integrated performance-based and participatory budgeting model offers a more effective and governance-oriented framework for improving institutional performance and financial accountability in Islamic boarding schools. The proposed model provides practical implications for policymakers and educational managers seeking to strengthen financial management in faith-based educational institutions.